Output Gap, Monetary Policy Trade-Offs and Financial Frictions - Francesco Furlanetto; Paolo Gelain; Marzie Taheri Sanjani (Norges Bank, 2017)
This paper investigates how the presence of financial frictions and financial shocks changes the definition and the estimated dynamics of the output gap in a New Keynesian model. Financial shocks absorb explanatory power from efficient labor supply shocks, thus changing radically the dynamics of the economy's efficient frontier. Despite their large impact on the output gap, financial factors affect the monetary policy trade-offs only to some extent. Nominal stabilization can be achieved at the cost of limited (but non-negligible) fluctuations in real economic activity. Finally, we discuss an alternative measure of the output gap (in deviation from the optimal equilibrium) that is a better measure of imbalances in the economy than the conventional output gap.
hdl:11250/2495583
Keywords: E32; C51; C52; 330; financial frictions; output gap; monetary policy